Low glycaemic diet and metformin therapy: a new approach in male subjects with acne resistant to common treatments. (1st January 2016) - Fabbrocini, G.; Izzo, R.; Faggiano, A.; Del Prete, M.; Donnarumma, M.; Marasca, C.; Marciello, F.; Savastano, R.; Monfrecola, G.; Colao, A.
Summary: Acne is a common and complex skin disease, with a very complex pathogenesis. Although in women the relationship between acne and insulin resistance is well known, in particular in women with PCOS, in males this relationship has been poorly investigated. In total, 20 subjects with an altered metabolic profile were considered for this study and randomized as follows: 10 patients were treated with metformin plus a hypocaloric diet for 6 months (group A), while 10 patients did not receive any treatment with metformin and were only followed up (group B). All patients of group A, after 6 months of metformin therapy, had a statistically significant improvement compared with patients in group B. Our study reveals the importance of diet and insulin resistance in acne pathogenesis, and underlines the possible use of metformin and diet as possible adjuvant therapy for male patients with acne.